Chemical profiling and cholinesterase inhibitory activity of five phaedranassa herb. (amaryllidaceae) species from ecuador - Moreno, Raúl (2020)
It is estimated that 50 million people in the world live with dementia, 60-70% of whom suffer from Alzheimer's disease (AD). Different factors are involved in the development of AD, including a reduction in the cholinergic neurotransmission level. The Amaryllidaceae plant family contains an exclusive, large, and still understudied alkaloid group characterized by a singular skeleton arrangement and a broad spectrum of biological activities. The chemistry and biodiversity of Ecuadorian representatives of the Phaedranassa genus (Amaryllidaceae) have not been widely studied. In this work, five Ecuadorian Phaedranassa species were examined in vitro for their activity towards the enzymes acetyl- (AChE) and butyrylcholinesterase (BuChE), and the alkaloid profile of bulb extracts was analyzed by GC-MS. The species Phaedranassa cuencana and Phaedranassa dubia showed the most AChE and BuChE inhibitory activity, respectively. To obtain insight into the potential role of the identified alkaloids in these inhibitory effects, docking experiments were carried out, and cantabricine showed in silico inhibitory activity against both cholinesterase structures. Our results show that Amaryllidaceae species from Ecuador are a potential source of new drugs for the palliative treatment of AD. © 2020 by the authors.